Implications of Baltic amber finds in northern Finland 4000–2000 BC - Núñez, Milton; Franzén, Patrik (Archaeologia Lituana, 2011)
Some time during the late 5th millennium cal BC (cal), East Baltic amber imports began to reach Finland, where it occurred associated with the so-called Typical Comb ware (TCW, c. 4100–3500 cal BC). Imports of this rare fossil resin continue through the remaining of the Finnish Middle Neolithic, but seem to dwindle by the end of the 3rd millennium BC (Äyräpää, 1945, 1960; Luho, 1962; Edgren, 1966, 1992; Siiriäinen, 1967; Rankama, 1977; Torvinen, 1979; Koivunen, 1996, 2006; Oikarinen, 1998; Franzén, 2009). [...]